Nomenclature in the field of food safety - Mykhailiutenko, S.; Yevstafieva, V.; Melnychuk, V.; Kuzmenko, L. (Scientific Progress & Innovations, 2025)
The food industry of Ukraine includes over forty different branches of production, including meat. It is important to guarantee the high quality of these products, since meat and meat products are an integral part of the daily human diet. For Ukraine, food security has become particularly acute under martial law, but monitoring is ongoing, including testing of meat raw materials. Every year, a significant amount of products are seized from meat processing plants and state agri-food laboratories in markets due to invasive diseases. The crowded keeping of animals of different ages in farms of different forms of ownership, insufficient funding directly affects the spread of parasitosic pathogens. Numerous publications confirm the circulation of helminthiasis precisely in small farms, where veterinary treatments are not systematically carried out, therefore post-mortem examination of animals is important for diagnosis. At the same time, it should be noted that in the process of constructing scientific names of invasive diseases, which contain Latin and Greek roots, and in the names of zooparasites, when determining their systematic position, inconsistency is often observed, which prevents the correct diagnosis of diseases and indicates a lack of clarity, clarity, and order in veterinary and sanitary assessment. Compliance with laws on a systematic basis requires a clearly defined framework for its regulation with an understanding of terminology. Therefore, the purpose of this study is to analyze the current legislation in the field of food safety, unification of parasitological terms. The authors analyzed national regulatory acts, orders and official publications. The article presents discrepancies in the names of diseases of invasive etiology. It is proven that the terminology provided in parasitology and veterinary-sanitary expertise does not fully correlate with each other: they define the names differently – old and new. The article determines the need to unify the names of invasive diseases according to the international classification, especially during post-mortem assessment of carcasses and slaughter products in case of suspicion or detection of invasive animal diseases. At the same time, the authors focus on the possible course of mixed invasions and, accordingly, the severity of the disease, the peculiarity of diagnostics, and sanitary indicators of livestock products. To improve existing legislative acts, it is advisable to review them with the involvement of narrowly specialized specialists, including parasitologists. Thus, the given unified examples of the nosology of helminthiasis, which comply with international rules, should be introduced into the educational process of higher educational institutions in both the discipline of parasitology and veterinary and sanitary expertise.